2008
DOI: 10.1002/j.0022-0337.2008.72.1.tb04453.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Ability to Assess Gingival Health Status with DAAGS Software

Abstract: The aim of this study was to evaluate the ability of dental students at different levels of education (Basic, Preclinic, and Clinic groups) to assess the level of gingival health status by using the Development of Ability to Assess Gingival Status (DAAGS) computer software program designed according to the Oral Rating Index (ORI) criteria. Two hundred and thirteen dental students at three levels of dental education voluntarily participated in three DAAGS tests in which they judged twenty-four photos. The three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…The correct score according to the GS of each photo was shown after the participants completed test 1; then, test 2 was conducted immediately. The time for judgment was ten seconds for each photo in both tests 7. The OnTime method in VBA was used to run a procedure periodically 8.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The correct score according to the GS of each photo was shown after the participants completed test 1; then, test 2 was conducted immediately. The time for judgment was ten seconds for each photo in both tests 7. The OnTime method in VBA was used to run a procedure periodically 8.…”
Section: Methodsmentioning
confidence: 99%
“…DAAGS test results were evaluated as follows on four measures7: correct answers were the number of correct answers out of twenty‐four photos; for five pairs of identical oral pictures, reproducibility indicated the number of pairs in which the examinee's diagnosis was the same; irrelevant answers were the number of cases in which an examinee's absolute value of diagnosis differed from the correct score according to the GS by three or more points; finally, each examinee received an overall ability score for each test separately. The overall ability scores were calculated according to the following criteria: 1) if the correct answers were more than eight but less than twelve, the examinee received one point; if twelve or more, the examinee received two points; 2) if the reproducibility was two pairs out of five pairs, the examinee received one point; if the reproducibility was three pairs or more, the examinee received two points; and 3) if the number of irrelevant answers was zero or one, the examinee received one point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also important is the fact that Basic group showed a significant improvement which indicates that the DAAGS software can be considered an instructive tool for education. Authors concluded that DAAGS would be useful to dental students before clinical training and also an helpful tool for calibration of dental employees (Camgoz, M., et al, 2008). Other application used on periodontoly learning stage is the Virtual Learning Environment (VLE), a web-based database application, divided into 6 sections (history taking, clinical examination, Xrays, diagnosis, treatment planning and prognosis, and log) where the learner uses free text communication on the screen to interact with patient data.…”
Section: Decision Support Systems/technologies Used During Learning Smentioning
confidence: 99%